Methods of examinations children with surgical pathology : clinical methodical guidance for english-speaking fifth-year students of medical faculty for clinical case report writing - Spakhi, O. V.; Zaporozhchenko, A. G.; Lyaturynska, O. V.; Makarova, M. A.; Запорожченко, Андрій Григорович; Спахі, Олег Володимирович; Лятуринська, Ольга Василівна; Макарова, Марина Олександрівна (Запорізький державний медичний університет, 2015)
The guidelines on teaching and methodology are designed as a manual for independently conducted treatment of children with surgical pathology and writing a training case history for the 5th year students of treatment and pediatric faculty during their training course in the clinic of pediatric surgery. The guidelines include aims of treatment, the plan of medical examination of a patient child, the plan of writing a case history. The appendix contains plans of medical investigation in various diseases and standard physiological and laboratory indicators, which are necessary to shape clinical thinking.